Auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption and its preparation method and application
Through electrostatic adsorption technology, calcium carbide slag and low-calcium fly ash react with industrial waste gas of carbon dioxide in rotary filler beds, and auxiliary gelling materials that efficiently store carbon dioxide, solving the low carbon dioxide storage efficiency and solid waste in the existing technology The problem of low utilization rate has achieved the replacement of low-carbon gelling materials.
Patent Information
- Application Number
- CN202410025232.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-01-08
AI Technical Summary
The existing technology has problems such as low efficiency, high energy consumption and low solid waste utilization in carbon dioxide storage, and high carbon emissions in the cement industry require the development of low-carbon gelling materials to replace it.
Calcium carbide slag and low-calcium fly ash are used as raw materials, and carbonization reaction with carbon dioxide-containing industrial waste gas in the rotary filler bed through electrostatic adsorption technology to prepare auxiliary gelling materials. This method is cheap, has high efficiency and low energy consumption, and can achieve efficient storage of carbon dioxide and resource utilization of waste such as fly ash.
The efficient storage and efficient resource utilization of carbon dioxide have been achieved. The prepared gelling materials have high compressive strength and fast settling time, which can replace some cement and reduce the carbon footprint of the cement industry.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to an auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation, and a preparation method and application thereof, belonging to the technical field of building materials. Background Art
[0002] The cement industry is a high-carbon emission industry, so there is an urgent need to develop low-carbon cementitious materials to replace cement.
[0003] Fly ash is a byproduct of coal-fired power plants; unused fly ash is stored in landfills, and improper treatment will pollute water sources and soil. The production of acetylene by the calcium carbide method will produce calcium carbide slag; the storage of calcium carbide slag will occupy a large amount of land, cause water resource pollution, and affect the surrounding ecological environment. Carbon dioxide, as the most important greenhouse gas, urgently needs to be effectively controlled. However, the existing carbon dioxide sequestration method has problems such as low efficiency, high energy consumption, low carbon dioxide sequestration efficiency, and long production time. Chinese patent document CN104759203A discloses a fluidized bed process for directly capturing carbon dioxide in mineralized flue gas, using high-calcium waste such as fly ash as raw materials, opening a bypass on the flue gas discharge flue to lead a flue gas through a temperature and humidity regulator to adjust the temperature and humidity, and the flue gas after temperature and humidity adjustment is contacted with the high-calcium waste in the fluidized bed reactor to generate calcium carbonate. After the reaction, the dusty gas leaving the fluidized bed reactor is sent to a cyclone separator for gas-solid separation, and the resulting gas is sent back to the original flue gas discharge flue and discharged into the chimney. The process of this invention can not only effectively improve the utilization of fly ash, but also reduce CO2 emissions from power plants; however, the solid waste involved in the reaction in this invention is single, and the utilization rate of solid waste is low. Chinese patent document CN101219330A discloses a process method and device for in-situ fixation of CO2 in flue gas that integrates multiple processes such as CO2 absorption and separation, carbonation fixation, and solid waste resource utilization; a supergravity rotating packed bed reactor is used to greatly improve the mass transfer absorption rate of CO2. However, this invention only prepares calcium carbonate products through carbonization reaction, and Ca 2+ The solid waste residues after leaching are still discarded, and the solid waste cannot be fully utilized. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an auxiliary cementitious material based on electrostatic adsorption for efficient carbon fixation, and a preparation method and application thereof. With carbide slag as a calcium source and low-calcium fly ash as a calcium source and matrix, carbide slag particles are electrostatically adsorbed on the surface of fly ash particles, and carbonization reaction occurs with industrial flue gas containing carbon dioxide of a certain humidity in a rotating packed bed device to prepare an auxiliary cementitious material. The method of the present invention has cheap and readily available raw materials, high efficiency, and low energy consumption; it can permanently seal carbon dioxide in industrial waste gas, with high carbon dioxide sealing capacity and sealing efficiency; and it fully realizes the resource recycling of waste materials such as fly ash. The cementitious system prepared by compounding the obtained auxiliary cementitious material and cement has higher strength and faster setting time, and is expected to replace more cement clinker to prepare low-carbon composite cement.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] A method for preparing an auxiliary gelling material based on electrostatic adsorption and efficient carbon fixation, comprising the steps of:
[0007] (1) placing ultrafine carbide slag powder in an electrostatic field to make it have static charge, thereby obtaining ultrafine carbide slag powder with static charge;
[0008] (2) low-calcium fly ash and ultrafine carbide slag powder with electrostatic charge are uniformly mixed and added to a rotating packed bed; industrial waste gas containing carbon dioxide and water vapor is continuously introduced into the rotating packed bed; after the reaction, the material is collected and dried to obtain an auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption.
[0009] Preferably, according to the present invention, in step (1), the particle size of the ultrafine carbide slag powder is 1000 mesh to 2500 mesh; the ultrafine carbide slag powder is prepared by drying and grinding carbide slag.
[0010] Preferably, according to the present invention, in step (1), the ultrafine carbide slag powder comprises the following components in parts by weight: 86.26-89.21 parts of CaO, 3.12-5.41 parts of SiO2, 4.01-6.75 parts of SO3, 1.39-2.27 parts of Al2O3, and 0.21-1.97 parts of MgO.
[0011] Preferably, according to the present invention, in step (1), the electrostatic field is generated by a discharge machine; the high-voltage rectifier converts 220V alternating current into high-voltage direct current, and the air is ionized to generate a large number of free electrons, which attach to the surface of the ultrafine calcium carbide slag powder to make it charged.
[0012] According to the preferred embodiment of the present invention, in step (2), the low-calcium fly ash is solid waste generated by a coal-fired power plant. The particle size of the low-calcium fly ash is 150 mesh to 500 mesh.
[0013] Preferably according to the present invention, in step (2), the low-calcium fly ash comprises the following components in parts by mass: 2.32-3.76 parts of CaO, 44.01-57.89 parts of SiO2, 23.24-31.34 parts of Al2O3, 2.27-5.15 parts of Fe2O3, and 0.63-3.97 parts of MgO.
[0014] Preferably according to the present invention, in step (2), the mass ratio of low-calcium fly ash to ultrafine carbide slag powder with electrostatic charge is 60-90:10-30.
[0015] According to the present invention, in step (2), during the mixing process, the electrostatic adsorption effect generated by the ultrafine carbide slag powder with static charge causes it to adsorb together with the low-calcium fly ash particles, and the carbide slag is evenly attached to the surface of the fly ash.
[0016] Preferably according to the present invention, in step (2), the continuous introduction rate of the industrial waste gas containing carbon dioxide and water vapor is 3-5 L / min.
[0017] Preferably, according to the present invention, in step (2), the industrial waste gas containing carbon dioxide and water vapor comprises the following components in volume percentage: water vapor 9-10%, carbon dioxide 25-26%, and nitrogen 60-61%; preferably, the industrial waste gas containing carbon dioxide and water vapor comprises the following components in volume percentage: water vapor 9.6%, carbon dioxide 25.4%, and nitrogen 60.5%.
[0018] Preferably, in step (2), the reaction time is 5-15 min, preferably 10 min; the rotation rate of the rotating packed bed is 300-500 r / min, preferably 500 r / min; the temperature of the rotating packed bed is 20-30°C, and the pressure is 0.05-0.5 MPa.
[0019] An auxiliary gelling material with high-efficiency carbon fixation based on electrostatic adsorption is prepared by the above method.
[0020] The above-mentioned auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption is used in concrete and / or mortar.
[0021] Preferably, according to the present invention, the auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation is compounded with cement and applied to concrete and / or mortar; preferably, the mass ratio of the auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation to cement is 20-40:60-80. The cementitious material of the present invention can replace the use of part of cement, reduce the carbon footprint of the cement industry, and alleviate the impact of greenhouse gases on the environment. At the same time, the nano calcium carbonate generated by the carbonization reaction can accelerate cement hydration and improve the early strength of cement-based materials.
[0022] The principle of the present invention is:
[0023] The carbonation reaction involves a series of physical and chemical processes. Based on the gas-liquid-solid three-phase reaction theory, it can be roughly divided into four stages. First, the water vapor in the industrial waste gas provides a liquid environment for the carbonation reaction. The calcium-based active substances in the carbide slag and fly ash dissolve and hydrolyze in water, releasing hydroxide ions, which increases the pH value of the slurry. The strong alkalinity of the slurry can efficiently capture carbon dioxide in the industrial waste gas; the carbon dioxide in the industrial waste gas dissolves in water to form carbonic acid, which reacts rapidly with the hydroxide ions and calcium ions in the slurry, causing the pH value of the slurry to begin to decrease and form calcium carbonate precipitation; as the mineralization reaction continues, the rate of hydrolysis to produce hydroxide ions gradually decreases below the rate of carbon dioxide to produce hydrogen ions. When the pH value of the slurry gradually decreases to 7 and remains unchanged, the carbonation reaction is basically completed.
[0024] CaO+H2O=Ca(OH)2
[0025] Ca(OH)2=Ca 2+ +2OH -
[0026]
[0027] Ca 2+ +CO3 2- =CaCO3
[0028] The technical features and beneficial effects of the present invention are:
[0029] (1) The present invention uses industrial solid wastes such as fly ash and carbide slag. The raw materials are cheap and easy to obtain, and the efficient resource recycling of fly ash and carbide slag is realized. The raw material particle size is small, which is conducive to the subsequent electrostatic adsorption and reaction, and is conducive to its filling effect. Ultrafine particles can improve the packing density of the cement cementitious system, replace the pore water between particles, increase the free water content, and be used for hydration reaction; the nano calcium carbonate generated during the carbonization process can fill the pores of the cement matrix to make the structure denser, and at the same time provide more nucleation sites for cement hydration, accelerate cement hydration, and improve early strength and durability.
[0030] (2) The present invention uses carbide slag as a calcium source and low-calcium fly ash as a calcium source and matrix. The carbide slag particles are electrostatically adsorbed on the surface of the fly ash particles, and carbonization reaction occurs with industrial flue gas containing carbon dioxide of a certain humidity in a rotating packed bed device to prepare an auxiliary cementitious material. The carbide slag particles are adsorbed on the fly ash particles by electrostatic action, which reduces the time of ion diffusion and prevents the generated calcium carbonate from agglomerating on the surface of the carbide slag to hinder the precipitation of internal ions, thereby improving the reaction efficiency and carbon dioxide storage capacity, and improving the compressive strength of the auxiliary cementitious material and the cement-based cementitious system. The fly ash is spherical, and the calcium carbonate generated by the carbonization of the carbide slag is partially ectopically attached to the surface of the fly ash. When the fly ash is added to cement, the side effects of nanomaterials on the workability of cement can be reduced. Through the material and chemical action of nano calcium carbonate, the hydration of cement can be accelerated, and the side effects of fly ash on the setting time and early strength of cement can be alleviated. If carbide slag is not electrostatically treated, the reaction rate will be slow, the carbonization efficiency and carbon dioxide storage capacity will be low, the workability of the obtained auxiliary cementitious material for cement will be significantly reduced, and its contribution to the acceleration of setting and strength development of composite cement materials will be reduced.
[0031] (3) The present invention uses a rotating packed bed as a reactor, and increases gas-liquid mass transfer through high centrifugal acceleration, thereby greatly improving the carbonization reaction rate.
[0032] (4) The method of the present invention is preferably directed to the specific composition of carbide slag powder and low-calcium fly ash of the present invention. If the composition is not suitable, the carbon dioxide storage capacity, the obtained auxiliary cementitious material and the compressive strength of the cement-based cementitious system and other properties will be reduced. The particle size of the carbide slag powder needs to be suitable. If it is not suitable, the carbon dioxide storage capacity, the compressive strength of the obtained auxiliary cementitious material and the cement-based cementitious system and other properties will also be reduced. The mass ratio of low-calcium fly ash to the ultrafine carbide slag powder with static charge, the rotation rate of the rotating packing bed, the temperature and pressure, etc. need to be suitable. If they are not suitable, the above-mentioned excellent effects of the present invention cannot be achieved. The method of the present invention as a whole, each step and each condition work together to achieve the excellent effects of the present invention.
[0033] (5) The method of the present invention can permanently seal carbon dioxide in industrial waste gas, with high carbon dioxide storage capacity and efficiency; and the reaction conditions in the preparation process are mild, with low energy consumption, high efficiency, no waste gas emission, and low water consumption, which is beneficial to mitigating global warming and protecting the environment. The cementitious material obtained by the present invention has high mechanical properties such as compressive strength, and is expected to be used as a low-carbon cementitious material to replace cement; the cementitious material obtained by the present invention and cement are compounded to effectively improve the mechanical properties such as compressive strength of the cement-based cementitious system, and have a faster setting time, and is expected to replace more cement clinker to prepare low-carbon composite cement. DETAILED DESCRIPTION
[0034] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, they will be described in detail below in conjunction with specific embodiments, but are not limited to these. Anything not fully described in the present invention shall be based on conventional techniques in the art.
[0035] In the embodiment, the ultrafine carbide slag powder includes the following components in percentage by weight: CaO 88.10wt%, SiO2 3.51wt%, SO3 5.77wt%, Al2O3 1.91wt%, and MgO 0.35wt%.
[0036] The low-calcium fly ash includes the following components in percentage by mass: CaO 2.56wt%, SiO2 57.25wt%, Al2O3 23.24wt%, Fe2O3 5.02wt%, and MgO 1.97wt%.
[0037] The industrial waste gas containing carbon dioxide and water vapor includes the following components in volume percentage: water vapor 9.6%, carbon dioxide 25.4%, nitrogen 60.5%, and other components 4.5%.
[0038] Embodiment 1:
[0039] A method for preparing an auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation comprises the following steps:
[0040] (1) drying and grinding carbide slag to obtain 1000 mesh ultrafine carbide slag powder, placing it in an electrostatic field generated by a discharge mechanism to make it have static charge, thereby obtaining ultrafine carbide slag powder with static charge;
[0041] (2) mixing low-calcium fly ash (150-500 mesh) and ultrafine carbide slag powder with static charge in a mixer for 5 minutes, so that the carbide slag is evenly attached to the surface of the fly ash, and the mass ratio of low-calcium fly ash to ultrafine carbide slag powder with static charge is 80:20. The fly ash enters the rotating packing bed through the feed port, and the electrostatic adsorption effect generated by the static charge of the ultrafine carbide slag powder causes the ultrafine carbide slag powder with static charge to adsorb together with the low-calcium fly ash particles;
[0042] (3) continuously passing industrial waste gas containing carbon dioxide and water vapor into the rotating packed bed at a flow rate of 4 L / min, turning on the rotating device, rotating at a speed of 300 r / min, controlling the temperature at 25° C., and controlling the pressure at 0.1 MPa;
[0043] (4) After reacting for 10 minutes, the slurry after the reaction flows out from the bottom of the reactor into a collection container, and the gas is discharged from the top of the rotating packed bed. The slurry after the reaction is filtered and dried to obtain an auxiliary cementitious material with high efficiency carbon fixation based on electrostatic adsorption.
[0044] Embodiment 2:
[0045] A method for preparing an auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation comprises the following steps:
[0046] (1) drying and grinding carbide slag to obtain 1000 mesh ultrafine carbide slag powder, placing it in an electrostatic field generated by a discharge mechanism to make it have static charge, thereby obtaining ultrafine carbide slag powder with static charge;
[0047] (2) mixing low-calcium fly ash (150-500 mesh) and ultrafine carbide slag powder with static charge in a mixer for 5 minutes, so that the carbide slag is evenly attached to the surface of the fly ash, and the mass ratio of low-calcium fly ash to ultrafine carbide slag powder with static charge is 80:20. The fly ash enters the rotating packing bed through the feed port, and the electrostatic adsorption effect generated by the static charge of the ultrafine carbide slag powder causes the ultrafine carbide slag powder with static charge to adsorb together with the low-calcium fly ash particles;
[0048] (3) continuously passing industrial waste gas containing carbon dioxide and water vapor into the rotating packed bed at a flow rate of 4 L / min, turning on the rotating device, rotating at a speed of 400 r / min, controlling the temperature at 25° C., and controlling the pressure at 0.1 MPa;
[0049] (4) After reacting for 10 minutes, the slurry after the reaction flows out from the bottom of the reactor into a collection container, and the gas is discharged from the top of the rotating packed bed. The slurry after the reaction is filtered and dried to obtain an auxiliary cementitious material with high efficiency carbon fixation based on electrostatic adsorption.
[0050] Embodiment 3:
[0051] A method for preparing an auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation comprises the following steps:
[0052] (1) drying and grinding carbide slag to obtain 1000 mesh ultrafine carbide slag powder, placing it in an electrostatic field generated by a discharge mechanism to make it have static charge, thereby obtaining ultrafine carbide slag powder with static charge;
[0053] (2) mixing low-calcium fly ash (150-500 mesh) and ultrafine carbide slag powder with static charge in a mixer for 5 minutes, so that the carbide slag is evenly attached to the surface of the fly ash, and the mass ratio of low-calcium fly ash to ultrafine carbide slag powder with static charge is 80:20. The fly ash enters the rotating packing bed through the feed port, and the electrostatic adsorption effect generated by the static charge of the ultrafine carbide slag powder causes the ultrafine carbide slag powder with static charge to adsorb together with the low-calcium fly ash particles;
[0054] (3) continuously passing industrial waste gas containing carbon dioxide and water vapor into the rotating packed bed at a flow rate of 4 L / min, turning on the rotating device, rotating at a speed of 500 r / min, controlling the temperature at 25° C., and controlling the pressure at 0.1 MPa;
[0055] (4) After reacting for 10 minutes, the slurry after the reaction flows out from the bottom of the reactor into a collection container, and the gas is discharged from the top of the rotating packed bed. The slurry after the reaction is filtered and dried to obtain an auxiliary cementitious material with high efficiency carbon fixation based on electrostatic adsorption.
[0056] Embodiment 4:
[0057] A method for preparing an auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation comprises the following steps:
[0058] (1) drying and grinding carbide slag to obtain 1500 mesh ultrafine carbide slag powder, placing it in an electrostatic field generated by a discharge mechanism to make it have static charge, thereby obtaining ultrafine carbide slag powder with static charge;
[0059] (2) mixing low-calcium fly ash (150-500 mesh) and ultrafine carbide slag powder with static charge in a mixer for 5 minutes, so that the carbide slag is evenly attached to the surface of the fly ash, and the mass ratio of low-calcium fly ash to ultrafine carbide slag powder with static charge is 80:20. The fly ash enters the rotating packing bed through the feed port, and the electrostatic adsorption effect generated by the static charge of the ultrafine carbide slag powder causes the ultrafine carbide slag powder with static charge to adsorb together with the low-calcium fly ash particles;
[0060] (3) continuously passing industrial waste gas containing carbon dioxide and water vapor into the rotating packed bed at a flow rate of 4 L / min, turning on the rotating device, rotating at a speed of 500 r / min, controlling the temperature at 25° C., and controlling the pressure at 0.1 MPa;
[0061] (4) After reacting for 10 minutes, the slurry after the reaction flows out from the bottom of the reactor into a collection container, and the gas is discharged from the top of the rotating packed bed. The slurry after the reaction is filtered and dried to obtain an auxiliary cementitious material with high efficiency carbon fixation based on electrostatic adsorption.
[0062] Embodiment 5:
[0063] A method for preparing an auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation comprises the following steps:
[0064] (1) drying and grinding carbide slag to obtain 2000 mesh ultrafine carbide slag powder, placing it in an electrostatic field generated by a discharge mechanism to make it have static charge, thereby obtaining ultrafine carbide slag powder with static charge;
[0065] (2) mixing low-calcium fly ash (150-500 mesh) and ultrafine carbide slag powder with static charge in a mixer for 5 minutes, so that the carbide slag is evenly attached to the surface of the fly ash, and the mass ratio of low-calcium fly ash to ultrafine carbide slag powder with static charge is 80:20. The fly ash enters the rotating packing bed through the feed port, and the electrostatic adsorption effect generated by the static charge of the ultrafine carbide slag powder causes the ultrafine carbide slag powder with static charge to adsorb together with the low-calcium fly ash particles;
[0066] (3) continuously passing industrial waste gas containing carbon dioxide and water vapor into the rotating packed bed at a flow rate of 4 L / min, turning on the rotating device, rotating at a speed of 500 r / min, controlling the temperature at 25° C., and controlling the pressure at 0.1 MPa;
[0067] (4) After reacting for 10 minutes, the slurry after the reaction flows out from the bottom of the reactor into a collection container, and the gas is discharged from the top of the rotating packed bed. The slurry after the reaction is filtered and dried to obtain an auxiliary cementitious material with high efficiency carbon fixation based on electrostatic adsorption.
[0068] Embodiment 6:
[0069] A method for preparing an auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation comprises the following steps:
[0070] (1) drying and grinding carbide slag to obtain 2500 mesh ultrafine carbide slag powder, placing it in an electrostatic field generated by a discharge mechanism to make it have static charge, thereby obtaining ultrafine carbide slag powder with static charge;
[0071] (2) mixing low-calcium fly ash (150-500 mesh) and ultrafine carbide slag powder with static charge in a mixer for 5 minutes, so that the carbide slag is evenly attached to the surface of the fly ash, and the mass ratio of low-calcium fly ash to ultrafine carbide slag powder with static charge is 80:20. The fly ash enters the rotating packing bed through the feed port, and the electrostatic adsorption effect generated by the static charge of the ultrafine carbide slag powder causes the ultrafine carbide slag powder with static charge to adsorb together with the low-calcium fly ash particles;
[0072] (3) continuously passing industrial waste gas containing carbon dioxide and water vapor into the rotating packed bed at a flow rate of 4 L / min, turning on the rotating device, rotating at a speed of 500 r / min, controlling the temperature at 25° C., and controlling the pressure at 0.1 MPa;
[0073] (4) After reacting for 10 minutes, the slurry after the reaction flows out from the bottom of the reactor into a collection container, and the gas is discharged from the top of the rotating packed bed. The slurry after the reaction is filtered and dried to obtain an auxiliary cementitious material with high efficiency carbon fixation based on electrostatic adsorption.
[0074] Embodiment 7:
[0075] A method for preparing an auxiliary cementitious material based on electrostatic adsorption and efficient carbon fixation comprises the following steps:
[0076] (1) drying and grinding carbide slag to obtain 2500 mesh ultrafine carbide slag powder, placing it in an electrostatic field generated by a discharge mechanism to make it have static charge, thereby obtaining ultrafine carbide slag powder with static charge;
[0077] (2) mixing low-calcium fly ash (150-500 mesh) and ultrafine carbide slag powder with static charge in a mixer for 5 minutes, so that the carbide slag is evenly attached to the surface of the fly ash, and the mass ratio of low-calcium fly ash to ultrafine carbide slag powder with static charge is 70:30. The fly ash enters the rotating packing bed through the feed port, and the electrostatic adsorption effect generated by the static charge of the ultrafine carbide slag powder causes the ultrafine carbide slag powder with static charge to adsorb together with the low-calcium fly ash particles;
[0078] (3) continuously passing industrial waste gas containing carbon dioxide and water vapor into the rotating packed bed at a flow rate of 4 L / min, turning on the rotating device, rotating at a speed of 500 r / min, controlling the temperature at 25° C., and controlling the pressure at 0.1 MPa;
[0079] (4) After reacting for 10 minutes, the slurry after the reaction flows out from the bottom of the reactor into a collection container, and the gas is discharged from the top of the rotating packed bed. The slurry after the reaction is filtered and dried to obtain an auxiliary cementitious material with high efficiency carbon fixation based on electrostatic adsorption.
[0080] Comparative Example 1:
[0081] A method for preparing a gelling material comprises the following steps:
[0082] (1) drying and grinding the carbide slag to obtain 2500 mesh ultrafine carbide slag powder;
[0083] (2) mixing low-calcium fly ash (150-500 mesh) and ultrafine carbide slag powder in a mixer for 5 minutes to mix them evenly, with the mass ratio of low-calcium fly ash to ultrafine carbide slag powder being 80:20, and entering the rotating packing bed through the feed port;
[0084] (3) continuously passing industrial waste gas containing carbon dioxide and water vapor into the rotating packed bed at a flow rate of 4 L / min, turning on the rotating device, rotating at a speed of 500 r / min, controlling the temperature at 25° C., and controlling the pressure at 0.1 MPa;
[0085] (4) After reacting for 10 minutes, the slurry after the reaction flows out from the bottom of the reactor into a collection container, and the gas is discharged from the top of the rotating packed bed. The slurry after the reaction is filtered and dried to obtain a gelled material.
[0086] Test Example 1
[0087] The carbon dioxide storage capacity of the gelling materials prepared in Examples 1-7 and Comparative Example 1 was tested, and the test results are shown in Table 1. The carbon dioxide storage capacity of the gelling materials was obtained by a thermogravimetric analyzer. At 600°C to 800°C, CaCO3 produced by carbonization decomposed into CaO and CO2, and the carbon dioxide storage capacity was obtained by weight loss.
[0088] Table 1 Carbon dioxide storage capacity of the gelling materials prepared in Examples 1 to 7 and Comparative Example 1
[0089]
[0090] Test Example 2
[0091] The standard mortar mechanical properties of the cementitious materials prepared in Examples 1-7 and Comparative Example 1 were tested, and the test results are shown in Table 2 below. Experimental conditions: 135 g of cementitious material and 315 g of PI 42.5 cement were mixed as a cementitious system, and mixed with 225 g of water and 1350 g of ISO sand according to the "Technical Specification for Application of Mineral Admixtures" (GB / T 51003-2014). According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021), after the specimen was demoulded, it was placed in water at 20°C ± 1°C for curing for 28 days.
[0092] At the same time, a control group was set up, namely:
[0093] Low-calcium fly ash / PI 42.5 cement group: 135 g of low-calcium fly ash (same composition as in the above example) and 315 g of PI 42.5 cement were mixed to form a cementitious system; other experimental methods were the same as above, and the 28d compressive strength was tested.
[0094] PI 42.5 cement group: 450 g of PI 42.5 cement was used as the cementitious system; other experimental methods were the same as above, and the 28d compressive strength was tested.
[0095] Table 2 Mechanical properties of standard mortars of cementitious materials prepared in Examples 1 to 7 and Comparative Example 1
[0096]
[0097] Test Example 3
[0098] The standard consistency water consumption and initial and final setting time of the cementitious materials prepared in Examples 1-7 and Comparative Example 1 were tested, and the test results are shown in Table 3. Experimental conditions: 150 g of cementitious material and 350 g of PI 42.5 cement were mixed as a cementitious system, and the standard consistency water consumption was obtained according to the "Test Method for Standard Consistency Water Consumption, Setting Time and Stability of Cement" (GB / T 1346-2011), and the initial and final setting time of the cementitious material were obtained according to the standard consistency water consumption.
[0099] At the same time, a control group was set up, namely:
[0100] Low calcium fly ash / PI 42.5 cement group: 150 g of low calcium fly ash (same composition as in the above embodiment) and 350 g of PI 42.5 cement were mixed as the cementitious system; other experimental methods were the same as above, and the water consumption for standard consistency, as well as the initial and final setting times were tested.
[0101] PI 42.5 cement group: 500 g of PI 42.5 cement was used as the cementitious system; other experimental methods were the same as above, and the water consumption for standard consistency, as well as the initial and final setting times were tested.
[0102] Table 3 Standard consistency water consumption and initial and final setting time of the cementitious materials prepared in Examples 1 to 7 and Comparative Example 1
[0103]
[0104] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing an auxiliary gelling material based on electrostatic adsorption for efficient carbon fixation, comprising the steps of: (1) placing the ultrafine carbide slag powder in an electrostatic field to make it have an electrostatic charge, thereby obtaining an ultrafine carbide slag powder with an electrostatic charge; The particle size of ultrafine carbide slag powder is 1000 mesh ~ 2500 mesh; The ultrafine carbide slag powder includes the following components by mass: 86.26-89.21 parts of CaO, 3.12-5.41 parts of SiO2, 4.01-6.75 parts of SO3, 1.39-2.27 parts of Al2O3, and 0.21-1.97 parts of MgO; (2) low-calcium fly ash and ultrafine carbide slag powder with electrostatic charge are mixed evenly and added to a rotating packed bed; industrial waste gas containing carbon dioxide and water vapor is continuously introduced into the rotating packed bed; after the reaction, the materials are collected and dried to obtain an auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption; The low-calcium fly ash includes the following components in parts by mass: 2.32-3.76 parts of CaO, 44.01-57.89 parts of SiO2, 23.24-31.34 parts of Al2O3, 2.27-5.15 parts of Fe2O3, and 0.63-3.97 parts of MgO; The mass ratio of low-calcium fly ash to ultrafine carbide slag powder with electrostatic charge is 60~90:10~30.
2. The method for preparing the auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption according to claim 1, characterized in that: In step (1), the ultrafine carbide slag powder is prepared by drying and grinding carbide slag.
3. The method for preparing the auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption according to claim 1, characterized in that: In step (2), the particle size of the low-calcium fly ash is 150 mesh to 500 mesh.
4. The method for preparing the auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption according to claim 1, characterized in that: In step (2), the continuous introduction rate of industrial waste gas containing carbon dioxide and water vapor is 3-5 L / min.
5. The method for preparing the auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption according to claim 1, characterized in that: In step (2), the industrial waste gas containing carbon dioxide and water vapor includes the following components in volume percentage: water vapor 9-10%, carbon dioxide 25-26%, and nitrogen 60-61%.
6. The method for preparing the auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption according to claim 1, characterized in that: In step (2), the reaction time is 5-15 min; the rotation rate of the rotating packed bed is 300-500 r / min; the temperature of the rotating packed bed is 20-30° C., and the pressure is 0.05-0.5 MPa.
7. An auxiliary cementitious material for efficient carbon fixation based on electrostatic adsorption, prepared by any one of the methods of claims 1-6.
8. Use of the auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption as claimed in claim 7 in concrete and / or mortar.
9. The use according to claim 8, characterized in that: The auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption is compounded with cement and applied to concrete and / or mortar; The mass ratio of the auxiliary cementitious material with high-efficiency carbon fixation based on electrostatic adsorption to cement is 20-40:60-80.
Citation Information
Patent Citations
Method and device for fixing CO2 in stack gas by solid castoff carbonatation
CN101219330A
Fluidized bed technology and fluidized bed system for directly capturing CO2 in mineralized flue gas
CN104759203A
Method for grinding solid waste to remove carbon dioxide
CN114907040A
Preparation method and application of ultrahigh-activity solid waste-based carbon sequestration auxiliary cementing material
CN117263536A